Patterns of resistance to AHAS inhibitors in Limnocharis flava from Malaysia - Zakaria, Norazu; Ahmad Hamdani, Muhamad Saiful; Jurami, Abdul Shukor (Czech Academy of Agricultural Sciences, 2018)
Limnocharis flava (L.) Buchenau is among the most problematic rice weeds in Malaysia and is also reported to have developed multiple resistance to AHAS inhibitor bensulfuron-methyl and synthetic auxin 2,4-D. In this study, resistance across different AHAS inhibitors was characterised in a L. flava population infesting rice fields in Pulau Pinang, Malaysia. Dose-response experiments were conducted to determine the level of resistance to sulfonylureas, imidazolinone, triazolopyrimidine, and pyrimidinyl-thiobenzoate. Cross-resistance across different AHAS inhibitors was observed in the resistant L. flava population, exhibiting a high level of resistance to bensulfuron-methyl, while exhibiting a moderate level of resistance to metsulfuron-methyl and a low level of resistance to pyrazosulfuron-ethyl and pyribenzoxim. However, all resistant L. flava individuals were still sensitive to imazethapyr, penoxsulam and bispyribac-sodium. Based on the results, it is likely that resistance to AHAS inhibitors in L. flava is conferred by target-site resistance mechanisms.